Environmental therapy: interface design strategies for color graphics to assist navigational tasks in patients with visuospatial disorders through an analytic hierarchy process based on CIE color perception - Li, Weicong; Ma, Shangbing; Liu, Yueling; Lin, Haopai; Lv, Huabin; Shi, Wenwen; Ao, Jinghui (Frontiers in Psychology, 2024)
Environmental therapy theory has been applied in the research of disease prevention, and the effectiveness of using color and graphic designs to assist patients with spatial orientation has been confirmed. Visual-spatial impairments are common symptoms associated with cognitive decline.However, the interaction and driving factors between these impairments and spatial color and graphic designs remain unclear. This paper first discusses the correlation between the characteristics of visual-spatial impairments and environmental factors and then investigates the color preferences of such patients based on the CIE 1976 color system and the Analytic Hierarchy Process (AHP).Subsequently, the paper explores spatial design strategies conducive to spatial orientation from the perspective of adaptability to pathological characteristics, utilizing case study analysis. Findings: 1) Pathological characteristics of visual-spatial impairments (such as difficulties in spatial orientation and spatial neglect) are related to environmental factors; 2) Emotional attachment factors play a key role in patients' perception of satisfaction with environmental colors; 3) Color associations have the potential to strengthen spatial memory. Additionally, interface designs with high luminance, low saturation, and clear color differentiation facilitate patients' recognition of space. This paper posits that spatial interface design is a feasible approach to assist with spatial orientation, and it achieves this through a mediating process that progresses from influencing visual stimuli to cognitive memory and then to behavioral orientation. The article provides insights into the operational feasibility of this method.